From Scrolls to Scrolling Sacred Texts, Materiality, and Dynamic Media Cultures - Anderson, Bradford A. (Judaism, Christianity, and Islam - Tension, Transmission, Transformation, 2020)
Using the digital turn as a starting point, the essays in this volume explore the materiality of sacred texts in Judaism, Christianity, and Islam, along with transitions between various media cultures and material forms. The essays explore how material factors have shaped the production and transmission of sacred texts, as well as impacting the way in which people engage with, use, and perform these texts, within and between religious traditions.